The Security Forces Employees’ Oath: Structural and Semantic Parameters (Linguostylistic Studies, 2020)
The article highlights the structural and semantic features of the oaths taken by the law enforcement and security agency employees and servicemen in Ukraine. The case study involves 12 oath texts. The method of linguistic and stylistic analysis allows identifying the typical lexemes in the semantic fields of oaths. The method of textual analysis is used to determine the structural organization of the oath texts.In the language etiquette of an employee or serviceman of some law enforcement agencies and security forces in Ukraine, an oath is a solemn official promise to comply with the obligations assumed by future employees or servicemen when entering a job or service. The texts of such oaths are marked by typical structures and peculiar semantic content. The author argues that the oaths taken by law enforcement servicemen and officers of the security forces are the same kind of professional oath and interprets them as such. The convincing argument is that having pronounced the oath, a person acquires the status of an employee or serviceman of a law enforcement agency, ie he/she swears to perform definite professional duties. Such oaths always have legal status.Structurally, the text of the oath consists of the established elements: the self-naming of the person taking the oath with the indication to his/her surname, name, and patronymic; mentioning the name of the law enforcement agency where the person will serve/work; who or to whom they swear to be faithful and devoted, to serve faithfully, and remain faithful to their duties. Usually, such objects in modern oaths are Ukraine and its people, in old times - God, the country's leadership or troops. The next traditional element of an oath is specification of the commitments, namely personal responsibilities, common to all employees or military personnel and specific per each type of the law enforcement agency, and moral obligations. In some texts, there are optional phrases of “self-oath”, regarding the awareness of the punishment in case of violation of the oath and appealing to God’s power to help keep the promise.
Keywords: oath; text semantics; text structure; typological and differential features